Love, sex, and disability : the pleasures of care - Rainey, Sarah Smith (Disability in society., 2011)
In this exploration of intimate relationships between people with physical disabilities and those without, Sarah Smith Rainey shatters the myth of sexless, burdensome partnerships -- and in its place reveals a rich and rewarding continuum of emotional and physical intimacies. Rainey draws on interviews, autobiographies, and films to show how disabled/nondisabled couples not only build mutually satisfying relationships by giving and receiving in equal measure, but also move beyond traditional gender roles to create new forms of sexual intimacy. She also takes note of the challenges these couples face. With sensitivity and clarity, she offers an unparalleled portrait of the lived experience of disability and sexuality.